Dividing paradise : rural inequality and the diminishing American dream - Sherman, Jennifer (University of California Press, 2021)
"Dividing Paradise tells the story of a rural American community whose economic growth resulted in increasing inequality and divisions between those who can and those who cannot achieve their rural visions of the American dream. Based on in-depth interviews and participant observation with individuals on both sides of the divide, the book explores the contributors to and impacts of this stark inequality that has become commonplace across the United States. It exposes the mechanisms by which inequality flourishes and by which Americans have come to believe that it is acceptable and deserved"--